2000
DOI: 10.2166/wst.2000.0033
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of landfill leachates by comparing advanced oxidation and coagulation-flocculation processes coupled with activated carbon adsorption

Abstract: This work compares two pre-treatments (coagulation-flocculation process (CF) and the Fenton oxidation Method (FE)) of the activated carbon adsorption process (AC) to optimize the removal of the organic compounds in landfill leachates. The content of organic compounds was measured in terms of three global parameters: colour, chemical oxygen demand (COD) and dissolved organic carbon (DOC). The result obtained in discontinuous reactor conditions showed an increase in colour removal from 1.5 to 2.0 times and a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This can be explained by the production of smaller and more easily adsorbable compounds during ozonation. The small size of the ozonation products increases their surface area for adsorption and their accessibility to the GAC micropores (Ramirez Zamora et al, 2000). In contrast, coagulation-flocculation is only efficient in removing humic acids, whereas fulvic acids remain in the leachate still reducing the adsorption capacity of GAC.…”
Section: Post-treatment Of Coagulated and Ozonated Effluent Using Gramentioning
confidence: 99%
See 2 more Smart Citations
“…This can be explained by the production of smaller and more easily adsorbable compounds during ozonation. The small size of the ozonation products increases their surface area for adsorption and their accessibility to the GAC micropores (Ramirez Zamora et al, 2000). In contrast, coagulation-flocculation is only efficient in removing humic acids, whereas fulvic acids remain in the leachate still reducing the adsorption capacity of GAC.…”
Section: Post-treatment Of Coagulated and Ozonated Effluent Using Gramentioning
confidence: 99%
“…GAC adsorption is thus more efficient in reducing a 254 from leachate pretreated with coagulation-flocculation than with ozonation. Though ozonation of bulk organic matter leads to the production of smaller compounds which are easily adsorbed (Ramirez Zamora et al, 2000), the by-products from oxidation of aromatic sites and carbon to carbon double bonds are very hydrophilic thus poorly adsorbed by GAC. On the contrary, infra red analysis of the chemical composition of the coagulated effluent reveals the presence of amines and aliphatic compounds (Monje-Ramirez and Orta de Velásquez, 2004).…”
Section: Post-treatment Of Coagulated and Ozonated Effluent Using Gramentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of leachate is given in Table 1. It is observed that presenting a relatively high value of COD and BOD 5 and the rate of COD/BOD 5 values indicates that the leachate can be defined as young. There has beeen low COD and BOD 5 concentrations according to the samples taken between January and December in 2006 depending on the monthly rainfall.…”
Section: Landfill Leachatementioning
confidence: 99%
“…Young leachate is characterized by chemical oxygen demand (COD) concentration higher than 5 g/L and by low nitrogen concentration (<400 mg/L of N). Old leachate is characterized by a high nitrogen concentration (>400 mg/L of N), high content of recalcitrant compounds and low biodegradable organic fraction (BOD 5 / COD 0.1) [4,5].…”
Section: Introductionmentioning
confidence: 99%